Integration of IoT technology, water hyacinth phytoremediation, and activated carbon for heavy metal contaminated water treatment - B. Azhar; H. Heryanto; A. R. Arif (International Journal of Environmental Science and Technology, 2026)

Epidemiological study of Crimean- Congo haemorrhagic fever in Thi Qar (2023–2024): assessing the role of tick bites, household animals, slaughter and fresh meat exposure in disease transmission - Saja Abdalkadhum Hommod; Azhar kareem Razzaq; Ali B. Roomi (VirusDisease, 2026)

Identifying the Worthy and Compatible Excipients Through In-Silico Approach for Rational Formulation Development: Insights into the Acyclovir and Trimethoprim Formulations - Abhijeet H. Patil; Meera C. Singh; Mohammed Sakib Musa; Minhaz Abdullah Al Mueid; Hossain Mohammed Reza; Md. Eshak Enan; Mahadie Hasan Jahad; Jamil Azhar Shakil; Shibam Mondal; Rajesh B. Patil (Journal of Pharmaceutical Innovation, 2025)

Sustainable integrated oil-palm livestock practice to enhance soil organic matter and carbon sequestration potential - Y. Umar; K. Sayed; M. I. Syakir; T. K. Al-Saedi; B. Azhar; K. A. Tohiran; F. Nobilly (International Journal of Environmental Science and Technology, 2025)

CamTrapAsia : A dataset of tropical forest vertebrate communities from 239 camera trapping studies - Calebe P. Mendes; Wido R. Albert; Zachary Amir; Marc Ancrenaz; Eric Ash; Badrul Azhar; Henry Bernard; Jedediah Brodie; Tom Bruce; Elliot Carr; Gopalasamy Reuben Clements; Glyn Davies; et al. (Ecology, 2024)
Information on tropical Asian vertebrates has traditionally been sparse, particularly when it comes to cryptic species inhabiting the dense forests of the region. Vertebrate populations are declining globally due to land‐use change and hunting, the latter frequently referred as “defaunation.” This is especially true in tropical Asia where there is extensive land‐use change and high human densities. Robust monitoring requires that large volumes of vertebrate population data be made available for use by the scientific and applied communities. Camera traps have emerged as an effective, non‐invasive, widespread, and common approach to surveying vertebrates in their natural habitats. However, camera‐derived datasets remain scattered across a wide array of sources, including published scientific literature, gray literature, and unpublished works, making it challenging for researchers to harness the full potential of cameras for ecology, conservation, and management. In response, we collated and standardized observations from 239 camera trap studies conducted in tropical Asia. There were 278,260 independent records of 371 distinct species, comprising 232 mammals, 132 birds, and seven reptiles. The total trapping effort accumulated in this data paper consisted of 876,606 trap nights, distributed among Indonesia, Singapore, Malaysia, Bhutan, Thailand, Myanmar, Cambodia, Laos, Vietnam, Nepal, and far eastern India. The relatively standardized deployment methods in the region provide a consistent, reliable, and rich count data set relative to other large‐scale pressence‐only data sets, such as the Global Biodiversity Information Facility (GBIF) or citizen science repositories (e.g., iNaturalist), and is thus most similar to eBird. To facilitate the use of these data, we also provide mammalian species trait information and 13 environmental covariates calculated at three spatial scales around the camera survey centroids (within 10‐, 20‐, and 30‐km buffers). We will update the dataset to include broader coverage of temperate Asia and add newer surveys and covariates as they become available. This dataset unlocks immense opportunities for single‐species ecological or conservation studies as well as applied ecology, community ecology, and macroecology investigations. The data are fully available to the public for utilization and research. Please cite this data paper when utilizing the data.

A comprehensive review on water pollution, South Asia Region: Pakistan - Rabeea Noor; Aarish Maqsood; Azhar Baig; Chaitanya B. Pande; Syeda Mishal Zahra; Abu Saad; Mariyam Anwar; Sudhir Kumar Singh (Urban Climate, 2023)

2-Methoxyestradiol inhibits carotid artery intimal hyperplasia induced by balloon injury via inhibiting JAK/STAT axis in rats - Ahmad S. Azhar; Ashraf B. Abdel-Naim; Osama M. Ashour (Environmental Science and Pollution Research, 2022)

DNA barcoding and genetic variability of earthworms (Clitellata: Oligochaeta) with new records from Mizoram, India - Azhar Rashid Lone; Samrendra Singh Thakur; Nalini Tiwari; Olusola B. Sokefun; Shweta Yadav (Organisms Diversity & Evolution, 2021)

Seaweed aquaculture: a preliminary assessment of biosecurity measures for controlling the ice-ice syndrome and pest outbreaks of a Kappaphycus farm - Cicilia S. B. Kambey; Iona Campbell; Elizabeth J. Cottier-Cook; Adibi R. M. Nor; Azhar Kassim; Ahemad Sade; Phaik E. Lim (Journal of Applied Phycology, 2021)
The application of biosecurity in seaweed aquaculture plays an important role in reducing the impact of disease and pest outbreaks. The continuous occurrence of seaweed pests including the macroalgal epiphytes, epi-endophytic filamentous algae and biofilms on Kappaphycus farms may also potentially induce further incidences of the ice-ice syndrome. In this study, on-farm biosecurity management measures were tested on the commercially grown seaweeds Kappaphycus malesianus and Kappaphycus alvarezii during peak ice-ice season at Gallam-Gallam Village, Sabah, Malaysia. The investigation was focused on preventative control measures including the early detection of the ice-ice syndrome and pests through propagule health checks, regular cleaning of the crop thallus and associated long-line ropes and monitoring of the environment. Farm procedures and practices were also assessed in terms of their biosecurity ‘risk’ using the hazard analysis and critical control point (HCCAP) approach. Observations were replicated in two different farm management systems; one system adopted routine biosecurity measures and the other had no biosecurity measures. The results showed that the ice-ice syndrome and pest outbreak was significantly decreased by 60–75% for K. malesianus and 29–71% for K. alvarezii at the farm which adopted the routine biosecurity measures compared with the no biosecurity treatment. The biosecurity measures also significantly improved growth rate and seaweed quality. The infection levels of the epi-endophyte Melanothamnus sp. contributed to the ice-ice syndrome in K. malesianus , whilst the epiphyte coverage was correlated to the ice-ice incidence in K. alvarezii . This study provides the first evidence of biosecurity management measures significantly decreasing the incidence of the ice-ice syndrome and pests on a commercial seaweed farm.

Clostridium culturomicium sp. nov. and Clostridium jeddahitimonense sp. nov., novel members of the Clostridium genus isolated from the stool of an obese Saudi Arabian - Hoang Thong Kieu; Noémie Garrigou; Amael Fadlane; Ludivine Brechard; Nicholas Armstrong; Philippe Decloquement; Muhammad Yasir; Esam Ibraheem Azhar; Saad B. Al-Masaudi; Jean-Christophe Lagier; Maryam Tidjani Alou; Didier Raoult (Current Microbiology, 2021)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Genetic characterization and diversity of circulating influenza A/H1N1pdm09 viruses isolated in Jeddah, Saudi Arabia between 2014 and 2015 - Anwar M. Hashem; Esam I. Azhar; Sarah Shalhoub; Turki S. Abujamel; Norah A. Othman; Abdulwahab B. Al Zahrani; Hanan M. Abdullah; Maha M. Al-Alawi; Anees A. Sindi (Archives of Virology, 2018)

Ecological impacts of oil palm agriculture on forest mammals in plantation estates and smallholdings - Badrul Azhar; David B. Lindenmayer; Jeff Wood; Joern Fischer; Mohamed Zakaria (Biodiversity and Conservation, 2014)

Transforming growth factor beta signaling in adult cardiovascular diseases and repair - Thomas Doetschman; Joey V. Barnett; Raymond B. Runyan; Todd D. Camenisch; Ronald L. Heimark; Henk L. Granzier; Simon J. Conway; Mohamad Azhar (Cell and Tissue Research, 2012)